1983
DOI: 10.1038/305050a0
|View full text |Cite
|
Sign up to set email alerts
|

Injection of GTP-binding protein or cyclic GMP phosphodiesterase hyperpolarizes retinal rods

Abstract: Light-induced activation of cyclic GMP phosphodiesterase (PDE) in the outer segments of vertebrate rod photoreceptors has been suggested as a step in the transduction process linking the absorption of light by rhodopsin with a hyperpolarization of the plasma membrane. Activation of PDE is mediated by a 'GTP-binding protein' (G). As a result of interaction with a rhodopsin photoproduct (possibly metarhodopsin II380), this GTP-binding protein exchanges a previously bound GDP for a GTP. This 'GTP-charged' protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

1986
1986
2008
2008

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…However, it should be emphasized that these studies do not exclude the PDE deactivation by P␥ phosphorylation, because ATP was omitted from their experimental conditions (39), or under their conditions the P␥ phosphorylation might have been suppressed due to the use of a P␥ mutant that can not interact with GTP/T␣ (40). We also note that using hydrolysis-resistant GTP analogs, electrophysiological studies have already suggested a GTP hydrolysis-independent PDE turnoff (41,42). Under their conditions, P␥ phosphorylation by Cdk5 could be a mechanism for the GTP hydrolysis-independent PDE turnoff.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it should be emphasized that these studies do not exclude the PDE deactivation by P␥ phosphorylation, because ATP was omitted from their experimental conditions (39), or under their conditions the P␥ phosphorylation might have been suppressed due to the use of a P␥ mutant that can not interact with GTP/T␣ (40). We also note that using hydrolysis-resistant GTP analogs, electrophysiological studies have already suggested a GTP hydrolysis-independent PDE turnoff (41,42). Under their conditions, P␥ phosphorylation by Cdk5 could be a mechanism for the GTP hydrolysis-independent PDE turnoff.…”
Section: Discussionmentioning
confidence: 99%
“…We also need to explore the regulatory mechanism of the P␥ phosphorylation by Cdk5. Moreover, electrophysiological study is required to show that Cdk5 is involved in the GTP hydrolysisindependent PDE turnoff described previously (41,42). Cdk inhibitors we used in this study will be useful for the electrophysiological study.…”
Section: Discussionmentioning
confidence: 99%
“…The number of Ga genes identified in most organisms is much greater than those identified for Go and G., which may be due to the relative ease of identification or perhaps to a lower number of G# and G. subunits due to the ability of different Ga subunits to interact with the same Gas complex. Some Ga subunits, such as the mammalian Gas or the Gat of transducin, appear to be the sole component required for activation of the effector and therefore the primary signal transducer of the heterotrimer (10,11). Many Ga genes have been identified from a diverse set of eukaryotic organisms (microbes, animals, and plants); however, in most cases relatively little is known about the signal transduction processes in which they function (refs.…”
mentioning
confidence: 99%
“…Gt-p[NH]ppG is functionally closer to Gt-GTP than to Gt-GDP because i) p[NH]ppG potently extracts Gt from ROS (16), ii) a light triggered near-infrared light scattering "dissociation signal" (presumably of Gt from R*) is observed in the presence of either GTP, p[NH]ppG, or GTP-γ-S, but not in the presence of GDP (6,11), iii) the dissociation constants for the Gt/GTP and Gt/ p[NH]ppG interactions are similar (11), iv) Gt-p[NH]ppG activates PDE while Gt-GDP does not (1,17), and v) limited trypsin proteolysis patterns of Gt-p[NH]ppG and Gt-GTP-γ-S are identical, while the proteolysis pattern of Gt-GDP is distinct (15,18,19). It appears, therefore, that there is little structural or functional difference between Gt-GTP and Gt-p[NH]ppG.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, it appears that Gt carrying a guanosine triphosphate moiety remains accessible to the activated receptor in both systems. It has been shown that Gt-p[NH]ppG, when injected into the toad rod outer segment, causes reversible membrane hyperpolarizations (17). Because p[NH]ppG is hydrolysis-resistant, one might expect that injection of Gt-p[NH]ppG would lead to a maintained activation of rod PDE and, thus, irreversibly hyperpolarize the membrane.…”
Section: Resultsmentioning
confidence: 99%